2017
DOI: 10.1149/2.0991709jes
|View full text |Cite
|
Sign up to set email alerts
|

Single Step Electrochemical Deposition of p-Type Undoped and Co2+Doped FeS2Thin Films and Performance in Heterojunction Solid Solar Cells

Abstract: Undoped and Co 2+ doped FeS 2 thin films (Co compositions are 1 to 5 mole%) were deposited on indium tin oxide glass substrate by a single step electrochemical deposition (ECD) method at low temperature (70 • C). Glancing angle X-ray diffraction (GAXRD) and Raman spectra showed that as-deposited undoped and Co 2+ doped FeS 2 thin films have a cubic pyrite structure without any trace of orthorhombic marcasite phase. Co 2+ doping does not affect the cubic structure of FeS 2 thin films with a strong (111) plane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…A further growth leads to a maximum at x = 0.3 and afterwards to a decrease. For large Co concentration the micro‐strain decreases and the NP behaves as undoped material . A similar behavior of M is observed in ref.…”
Section: Numerical Results and Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…A further growth leads to a maximum at x = 0.3 and afterwards to a decrease. For large Co concentration the micro‐strain decreases and the NP behaves as undoped material . A similar behavior of M is observed in ref.…”
Section: Numerical Results and Discussionsupporting
confidence: 86%
“…This difference gives rise to a tensile strain. Prabukanthan et al have reported that the lattice parameter in Co doped FeS 2 thin films grows up with increasing Co doping and then drops down. From here we conclude that the micro‐strain increases at first and after it decreases.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, all these advantages facilitated the fabrication of high-quality Sb 2 Se 3 films, leading to increased V OC , J SC as well as FF (VTD: 0.42 V, 29.9 mA cm −2 , 60.4% vs. RTE: 0.39 V, 25.3 mA cm −2 , 56.4%). The champion device achieved the efficiency record 7.6%, much higher than SnS, Cu 2 O and FeS 2 solar cells which have been studied for many years 4749 . The fabrication of record efficiency Sb 2 Se 3 solar cells employing vapor transport deposition, a technique with proven high turnaround and low cost for commercial CdTe solar cells, further strengthens the great potential of our Sb 2 Se 3 thin film photovoltaics.…”
Section: Discussionmentioning
confidence: 93%